The Expermintal Infection of L.monocytogenes &Isolation it from Egg, Oviduct & Ovary - Al-Jeboury, Nagham Mohammed (The Iraqi Journal of Veterinary Medicine, 2007)
The aim of the present study to detect the transmission of L.monocytogenesfrom experimental infected chickens to Egg products ,Ovary,Oviduct.&histopathological changes in these organs.2groups of chickn ,1st group(12 animals)infected with L.monocytogenes1ml/chick.SC,(1×1010 cfu/ml),2nd group injected 1ml/chick normal salin ascontrol.eggs were collected for isolate Listeria ,animal killed in(7,15,24,30,34,39,42)days,for isolateListeria from ovary,oviduct&samplestaken for histopathological examination.The results show theres no characterstic signs in infected chickens exceptdepression,anoxia&and theres marked decrease of egg production,qualititativly & quantitativly.L.monocytogenes isolated from egg ( shell, ,yolk,albumine)&persiste to(31,28&19) dayses respectively,also Listeria isolate from ovary&oviduct inchickens which killed in (7,15,24,30)day,&not isolate from chickens thatkilled in day (39,34,42)or in control.The histopathological changes theres congestion of the organs ,diffuseinfiltration of infilammatory cells such as lymphocyte , neutrophils &macrophage. also theres odeama, multi necrosis foci &desqumation.